Fluorescent Protein Production, Purification, and Coupling to Microspheres. Issue 4 (18th April 2023) - Dramicanin, Marija; Lim, Kevin; Monard, Simon
Abstract: Fluorescent proteins (FPs) have become an essential tool for biological research. Since the isolation and description of green FP, hundreds of FPs have been discovered and created with various characteristics. The excitation of these proteins ranges from ultraviolet (UV) up to near infrared (NIR). Using conventional cytometry, with each detector assigned to a fluorochrome, great care must be taken when selecting the optimal bandpass filters to minimalize the spectral overlap as the emission spectra of FPs are broad. Full‐spectrum flow cytometers eliminate the need to change optical filters for analyzing FPs, which simplifies instrument setup. In experiments where more than one FP is used, single‐color controls are required. These can be cells expressing each of the proteins separately. In the case of the confetti system, for instance, when four FPs are used, all these proteins will need to be expressed separately so that compensation or spectral unmixing can be performed, and this can be inconvenient and expensive. An appealing alternative is to produce FPs in Escherichia coli, purify them, and covalently couple them to carboxylate polystyrene microspheres. Such microspheres are ready to use and can be stored at 4°C for months or even years without any deterioration in fluorescence. The same procedure can be used to couple antibodies or other proteins to these particles. Here, we describe how to express and purify FPs, how to couple them to microspheres, and how to evaluate the fluorescent properties of the particles. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Escherichia coli expression and purification of recombinant mPlum Basic Protocol 2 : Coupling fluorescent proteins to polystyrene microspheres Support Protocol 1 : Comparing the cell‐bound and bead‐bound fluorescence signatures Support Protocol 2 : Comparing spectral signatures via the similarity index, complexity matrix, and spillover spread matrix of fluorescent protein–coupled beads